Quantificação e classificação dos resíduos da construção e demolição no município de Passo Fundo-RS - Bernardes, Alexandre (2006)
In function of the great amount of production of residues of the construction and demolition, one becomes basic to congregate information on the generation, and later classification for management of the reutilization and recycling of construction residues and demolition, approaching aspects as, place of generation and types of generated residues. Through research in loco in companies residues of the construction and demolition, had been quantified, identified and classified the residues proceeding from the city of Passo Fundo/RS. The loads residues collected during 03 months of the year had been catalogued, identifying the types of residues generated in the city, the loads had been classified in five types of origin of generation, being, land cleanness, rude land of hollowings, reforms and demolitions, residential reforms and building under construction. After the quantification of the generation, had been analyzed loads proceeding from Residues os Construction and Demolition, where manual separation and weighing of types of residues of each load had been classified through. They had been identified and classified the residues in accordance with the resolution of CONAMA nº 307